Effect of Common Bean (Phaseolus vulgaris L.) Varieties and Variable Rates of Potassium Fertilizer on Yield and Yield-Related Traits at Areka, Southern Ethiopia - Gobeze Loha; Merkineh Silas; Gifole Gidago (Applied and Environmental Soil Science)
Yield and yield components of common bean varieties reacted differently in response to variable levels of potassium (K) fertilization under different growing areas. Hence, it is necessary to integrate varieties with optimum K rates in order to maximize bean yield. On the other hand, insufficient K supply has a negative influence on stomata’s functionality, delaying stomatal closure and leaving pores partially closed. Thus, it is essential to find high-yielding varieties with balanced K fertilization. To evaluate common bean varieties at various K rates, a field experiment was carried out during the 2019/20 cropping seasons at the Areka Agricultural Research Center Experimental Field in Southern Ethiopia. Treatments consisted of three common bean varieties (SER 119, SAB 736, and Awassa Dume) and five K rates (0, 10, 20, 30, and 40 kg/ha K2O) combined in factorial and laid out in a randomized complete block design with three replications. The phenological, growth, yield components, and yield of common bean varieties reacted differently to the varieties, K rates, and their interactions. Parameters such as branches per plant, leaf area, LAI, pods per plant, biomass, and grain yield were significantly affected by varieties, K rates, and their interactions. Conversely, plant height, seeds per pod, and HI were significantly affected only by the main effects of varieties and K fertilizer rates. This investigation indicated that variety SER 119 exhibited superior performance over others with the highest grain yield at K rate of 40 kg/ha. Hence, variety SER 119 at K rate of 40 kg/ha could be used for production in the study area and similar agroecologies.